2016
DOI: 10.1016/j.jclepro.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from open-type anaerobic wastewater treatment system in natural rubber processing factory

Abstract: We evaluated greenhouse gases (GHGs) emissions from an open-type anaerobic system (OAS) treating ribbed smoked sheets (RSS) wastewater in a processing factory. The emitted biogas comprised 57.7%-60.8% methane, 14.5%-31.5% carbon dioxide, 10.8%-24.7% nitrogen, and 329-423 ppm of nitrous oxide. In the OAS, the chemical oxygen demand (COD) degraded as the methane emission rate increased from influent to effluent. Finally, 94.4% of the total COD was removed. More than 90% of the removed COD converted to methane. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The proliferation of Methanosaeta in group II showed correlation between the microbiomes and the degradable COD in terms of the VFA variation and gas production. Although, among acetoclastic methanogens Methanosarcina typically predominates over Methanosaeta at high acetate concentrations because of their considerably higher maximum specific utilization rate [26], Methanosaeta predominated over Methanosarcina in the sludge of the anaerobic reactors treating rubber wastewater [5][6][7]10]. The result from the relative rates between these two methanogens in this study is in good agreement with those reported previously.…”
Section: Microbial Community Structure In the Abrsupporting
confidence: 89%
See 2 more Smart Citations
“…The proliferation of Methanosaeta in group II showed correlation between the microbiomes and the degradable COD in terms of the VFA variation and gas production. Although, among acetoclastic methanogens Methanosarcina typically predominates over Methanosaeta at high acetate concentrations because of their considerably higher maximum specific utilization rate [26], Methanosaeta predominated over Methanosarcina in the sludge of the anaerobic reactors treating rubber wastewater [5][6][7]10]. The result from the relative rates between these two methanogens in this study is in good agreement with those reported previously.…”
Section: Microbial Community Structure In the Abrsupporting
confidence: 89%
“…Arcobacter, which grows under microaerophilic conditions, is a facultative anaerobic bacterium that reduces nitrate to nitrite [23]. In addition, Tanikawa et al have reported that ammonia was oxidized to nitrate and nitrite at the surface of an open-type anaerobic baffled lagoon [10]. Therefore, ammonia in the wastewater can be oxidized or retained in the influent and utilized by Arcobacter.…”
Section: Microbial Community Structure In the Abrmentioning
confidence: 99%
See 1 more Smart Citation
“…The process performance of existing open-type wastewater treatment systems in natural rubber processing factories Tanikawa et al investigated the process performance of four existing treatment systems for treating natural rubber processing wastewater in Thailand (one factory) and Vietnam (three factories) [11][12][13]. These factories applied the open-type, anaerobic-aerobic system for wastewater treatment (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…5 In the treatment of wastewater from natural rubber processing, the compartments of the ABR near the inlet serve as rubber traps from which rubber material can be recovered and reactor clogging can be prevented. 6,7 Previous studies describe the treatment of sulfate-rich wastewater including molasses and concentrated latex wastewater using a two-stage system that separates the biodegradation process into a sulfate reduction phase and a methane production phase to prevent hydrogen sulfide inhibition of methane-producing archaea. [3][4][5][6][7][8] The ABR, on the other hand, can separate the sulfate-reduction and methane-production phases using different compartments within a single-stage reactor.…”
mentioning
confidence: 99%